Share
Explore BrainMass

Expressing Roots of Quadratic Equations

If (x + 2)(x - 4) = 0 indicates that x + 2 = 0 or x - 4 = 0, explain why (x + 2)(x - 4) = 6 does not mean x + 2 = 6 or x - 4 = 6. Could we solve the equation using x + 2 = 3 and x - 4 = 2 because (3)(2) = 6?

Solution Preview

First let us understand why (x + 2)(x - 4) = 0 indicates that x + 2 = 0 or x - 4 = 0

From the properties of numbers, we know that, any real number multiplied by zero results zero.
i.e., a*0=0 for any real number a.
Product of any two non zero numbers yields us a non ...

Solution Summary

The allowable expressions for roots of quadratic equations are explained.

$2.19